History of Science: The Contribution of Muslims in Developing Modern Hospital System - Ali Khan, Feroz (International Journal of Pathology, 2020)
The hospital was one of the most developed institutions of medieval Islam and one of the high-water marks of the Muslim civilization. The hospitals of medieval Islam were hospitals in the modern sense of the word.1 Piety and Philanthropy cannot very well be divorced in medieval Islam, but by observing the Muslim hospitals and other institutions of charity and social welfare it is seen quite clearly that the idea of public assistance had developed beyond what piety alone could have produced. A discriminating and comprehensive consideration of the necessity of public assistance and social welfare, beyond mere religiosity, may be said to have been responsible for the quality and quantity of the hospitals of Islam.